2019
DOI: 10.2147/jmdh.s226011
|View full text |Cite
|
Sign up to set email alerts
|

<p>Resilience In Nepalese Adolescents: Socio-Demographic Factors Associated With Low Resilience</p>

Abstract: BackgroundResilience can be viewed as the potential to deal with stress positively. Resilient adolescents are likely to enter adulthood with a greater capacity to cope well in difficult circumstances. The purpose of this study was to measure resilience and the socio-demographic characteristics of Nepalese adolescents with low resilience.MethodsA cross-sectional study of 4 randomly selected secondary schools in Lalitpur, Nepal, was conducted with 416 adolescent students (54.8% girls; M=16.1 years, SD=1.5). Resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
(34 reference statements)
2
6
0
1
Order By: Relevance
“…The questionnaire is rather long, but if it is to have the ability to cover all the domains involved in the ecological theory system model this is perhaps necessary since resilience is a complex concept and must be seen in the context of the whole system complex. It should be noted that, in this study, it was shown that girls scored significantly lower on the ARQ, which also has been found in a previous study in Nepal [51], but also on the SOC-13, and Rosenberg's Self-Esteem Scale, and also scored lower on the secure attachment style. Although beyond the scope of this paper, this is something that ought to be investigated in future studies, including trauma experiences, since we know from earlier studies that interpersonal traumas are more frequent among girls [1] and that there are clear associations between both psychological distress and lowered self-esteem [52] and traumatic experiences.…”
Section: Discussionsupporting
confidence: 90%
“…The questionnaire is rather long, but if it is to have the ability to cover all the domains involved in the ecological theory system model this is perhaps necessary since resilience is a complex concept and must be seen in the context of the whole system complex. It should be noted that, in this study, it was shown that girls scored significantly lower on the ARQ, which also has been found in a previous study in Nepal [51], but also on the SOC-13, and Rosenberg's Self-Esteem Scale, and also scored lower on the secure attachment style. Although beyond the scope of this paper, this is something that ought to be investigated in future studies, including trauma experiences, since we know from earlier studies that interpersonal traumas are more frequent among girls [1] and that there are clear associations between both psychological distress and lowered self-esteem [52] and traumatic experiences.…”
Section: Discussionsupporting
confidence: 90%
“…In the BRS, almost 40% of the participants showed low resilience, associated with being in the third or fourth year of pharmacy study, smoking, and the consumption of caffeinated beverages. Previously, low resilience in adolescents was significantly associated with the female gender, attending a private school, higher birth order compared to first born, urban residence, and physical inactivity [ 62 ]. Among health professionals, resilience was described as multifaceted, adjoining discrete personal traits in addition to social and workplace features [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to reduce gender inequality, women/girls in Nepal are still marginalized in society (e.g., discrepancy in the available roles, priorities, opportunities, and resources) which affects their health, development and well-being [ 85 ]. Another study on resilience in Nepalese adolescents indicated that one-fifth of the students had low resilience and girls had a lower total resilience score [ 86 ]. Here, in this single cross-sectional study, with our main aim of how to promote self-esteem and prevent suicidal behavior in adolescents, we could not determine the exact rationale for the effect of SES on parents’ practice; thus, a future study should explore why this is the case.…”
Section: Discussionmentioning
confidence: 99%